MELAS syndrome with mitochondrial tRNA(Leu(UUR)) gene mutation in a Chinese family. Issue 5 (May 1994) - Huang, C C; Chen, R S; Chen, C M; Wang, H S; Lee, C C; Pang, C Y; Hsu, H S; Lee, H C; Wei, Y H
Abstract : The clinical features of a patient in a Chinese family with mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS syndrome) are reported. The study revealed that hearing and visual impairments and miscarriages may be early clinical presentations in MELAS. A heteroplasmic A to G transition in the tRNA(Leu(UUR)) gene was noted at the nucleotide pair 3243 in the mitochondrial DNA of muscle, blood, and hair follicles of the proband and his maternal relatives. Quantitative analysis of the mutated mitochondrial DNA revealed variable proportions in different tissues and subjects of maternal lineage in the family. Muscle tissue contained a higher proportion of the mutant mitochondria than other tissues examined. The function of the reproductive system of the proband seems to be impaired. In one clinically healthy sibling, the 3243rd point mutation was found in sperm mitochondrial DNA, although sperm motility was not affected. It seems that biochemical defects in mitochondrial respiration and oxidative phosphorylation are tissue specific expressions of the 3243rd point mutation in the mitochondrial DNA of the affected target tissues.